Impact of COVID-19 outbreak on dermatology services: Dermatology in isolation - Damevska, Katerina; Neloska, Lenche; Simeonovski, Viktor; Petrov, Andrej; Dimitrovska, I.; Teovska-Mitrevska, Natasha; Najdova, Anita; Polozhani, Nora (Wiley, 2020)
The current pandemic of COVID-19 demanded fast reorganization, as well as the necessity to adapt existing and administered extraordinary working protocols of dermatological services worldwide. We present a unique experience from Republic of Macedonia where an abrupt interruption of the dermatology service on a national level, and the COVID-19 outbreak, occurred simultaneously, with a significant impact on the quality of care.